Papers - Philadelphia Meeting – October, 1929 - Absorbability of Gases in Casting Copper and Effect of Adding Cuprosilicon (With Discussion) - O. W. Ellis (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
The question of the influence of gases upon the properties of copper has received the attention of a number of investigators, among whom Sieverts,' Iwase,2 Lobley and Jepson3 stand preeminent. Solubility of Gases in Copper Sieverts and Iwasé concerned themselves with the solubility of a variety of gases in the metal in the solid and liquid states. They determined the absorption coefficients of these gases and in all cases found a sharp change in solubility at the melting point of the metal. In this respect they disagree with Lobley and Jepson, who have based their opinions upon the appearance of small ingots of the metal which had been fused in an atmosphere of one or other of three gases and had then been rapidly cooled, while surrounded by gas, to the freezing point (rate—possibly 30" to 60" C. per sec.). The ingots that had been fused and cooled under nitrogen and carbon monoxide were free from blowholes and it was assumed that these gases were not absorbed in amounts much in excess of those which would dissolve in the solid metal; the ingots similarly treated under hydrogen were full of blowholes and it was assumed in this case that gas was ejected on solidification of the copper. The effect of varying the rate of freezing upon the character of the test ingots was not examined by these investigators; otherwise, it is felt, their views might have been subject to modification. Sieverts' most important contribution is that the solubility of a gas in any metal is proportional to the square root of its pressure or concentration. Knowing then the absorption coefficients of the various gases in copper, it should be possible to determine the analysis of the